The transfusion of non‐prophylactically RH‐KEL1 antigen‐matched red blood cells is feasible in selected myelodysplastic syndrome and acute myeloid leukaemia patients. Issue 5 (5th January 2022) - Xhaard, Aliénor; Miekoutima, Elsa; Pirenne, France; François, Anne; Tiberghien, Pierre; Sebert, Marie; Adès, Lionel; Fenaux, Pierre; Leprêtre, Anne‐Claire
Abstract: Background and Objectives: Most myelodysplastic syndromes (MDS) patients become red blood cell (RBC) transfusion‐dependent. Transfusing MDS patients with prophylactically RH‐KEL1 antigen‐matched (PAM) RBC units is recommended to avoid RBC allo‐immunization. D+C−E−c+e+, D+C−E+c+e− and D+C+E−c−e+ phenotypes are infrequent among French blood donors. To preserve infrequent phenotype RBC units for patients other than MDS, and to manage frequent phenotype RBC unit stocks, we let, for 1 year, higher‐risk non‐immunized chronically transfused MDS and acute myeloid leukaemia (AML) patients receive RBC transfusions matched only for D. Our objectives were to evaluate the impact of non‐PAM transfusions on the transfusion policy (which would be modified in case of RBC allo‐immunization) for frequent and infrequent phenotypes patients and to estimate the number of infrequent phenotypes RBC units that could be redistributed to other patients. Results: Ninety patients were enrolled. Thirty‐five patients had infrequent phenotypes, nine received only PAM RBC (143 units) and 26 PAM and non‐PAM RBC (415 and 532, respectively): none developed allo‐immunization. Fifty‐five patients had frequent RBC phenotypes, 34 received only PAM RBC (561 units) and three developed antibodies (2 non‐RH‐KEL1 and one anti‐E); 21 received PAM and non‐PAM RBC (436 and 109, respectively) and one developed allo‐immunization (unknown specificity). Our strategy enabled us to preserve 532 infrequent phenotypes RBC units: 216 D+C−E−c+e+, 33 D+C−E+c+e− and 283 D+C+E−c−e+ units, representing 48.8% of the total number of RBC units received by infrequent phenotypes patients during the study period. Conclusion: Allowing the transfusion of non‐PAM RBC in selected chronically transfused MDS and AML patients was feasible and enabled to redistribute infrequent phenotypes RBC units to other patients in need.